Social Engagement and Urban–Rural Disparity in Self-Management Behaviors: Study of Middle-Aged and Older Chinese Hypertension Patients - Lu, Jiao; Liu, Linhui; Wang, Yuan; Zhou, Zhongliang (Frontiers in Public Health, 2022)
Background: This study examines the effect of social engagement on urban–rural disparities in self-management behaviors (medication use, self-monitoring, physical activity, and tobacco and alcohol avoidance) among middle-aged and older Chinese patients with hypertension. Methods: Data from 2011 to 2018 were extracted from the four latest waves of the China Health and Retirement Longitudinal Study. Chi-square tests and t-tests were performed to examine urban–rural gaps in self-management behaviors. Random-effects panel logit regression models were adopted to confirm the effect of social engagement on urban–rural disparity in self-management behaviors and to explore whether this effect has narrowed or widened with “bilateral flow” between urban and rural residents. A Fairlie decomposition technique was also used to calculate the extent to which social engagement reflects urban–rural disparities. Results: There was significant urban–rural disparity in medication use and tobacco avoidance behaviors among the sampled patients. Medication use behavior (p < 0.001) among urban middle-aged and older patients was significantly better, whereas tobacco avoidance behavior (p < 0.05) was significantly lower compared with the rural population. Social engagement significantly enlarged the urban–rural gap in tobacco avoidance behavior (p < 0.01), but significantly narrowed the urban–rural gap in medication use behavior (p < 0.001). The Fairlie decomposition revealed that approximately 75.000% and 29.412% of the explained urban–rural gap in tobacco avoidance and medication use, respectively, could be attributed to social engagement. The negative effect of social engagement on urban–rural disparity in medication use increased when urban residents moved to rural areas (p < 0.05). Conclusions: The urban–rural disparities in self-management behaviors of middle-aged and older Chinese hypertensive patients were mainly manifested in medication use and tobacco avoidance behaviors. The gaps in these two behaviors partly changed with social engagement, while the migration of urban population to rural areas weakens the positive role of social engagement in narrowing the urban–rural gap in medication use behavior. The insights of this paper on social engagement and urban–rural disparity in self-management behaviors, and the effect of urban–rural migration thereof, deserve the attention of health policymakers and researchers.